Intrabacterial activity of type 3 secretion system effectors - Hasan, Md Kamrul (Kansas State University, 2023)
Gram-negative enteric pathogens are a major source of infection and disease all over the world. Understanding the pathogenesis mechanisms of enteric pathogens is critical for developing strategies to reduce dissemination, infection, and mortality. The sophisticated secretion system known as the Type 3 Secretion System (T3SS) is one of the key virulence strategies shared by major gram-negative enteric pathogens. T3SS is used by pathogens to deliver special effector proteins to the host cell. These effector proteins, as the term implies, target many eukaryotic cellular pathway components to modulate host response during infection, resulting in increased pathogen survivability. T3SS effectors are presumed to be inactive until they are injected into host cells and fold into active conformations. We previously discovered that the T3SS effectors NleB and SseK1 glycosylate Citrobacter rodentium and Salmonella enterica proteins, respectively, increasing resistance to environmental stress. A new class of T3SS effectors was investigated for potential intrabacterial activity in Chapter 2. The purpose of this study was to determine whether the T3SS effector proteases NleC, NleD, and EspL are active in C. rodentium. To accomplish this, we expressed in C. rodentium the best-characterized mammalian substrate of NleC, the NF-B p65 subunit; the substrate of NleD, JNK; and the substrates of EspL, RIPK1 and RIPK3 and monitored their proteolytic cleavage as a function of effector activity. NleC cleaved p65 intra-bacterially. As a result, we conclude that NleC, in addition to NleB, is enzymatically active within C. rodentium. Furthermore, T3SS effector EspL cleaved recombinant RIPK1, whereas NleD failed to cleave recombinant JNK protein, indicating that EspL is enzymatically active inside the pathogen, but NleD is not. The presence or absence of N-terminal Signal Peptides in the tested effectors was identified as a potential indicator of intrabacterial activity. To identify the potential target of NleC, we used a recombinant target protein cleavage assay, RNA sequencing, and a unique proteomics-based technique. Our group discovered intrabacterial activity and several bacterial targets of the T3SS effector NleB and its ortholog SseK1. The previously known intrabacterial activity of the T3SS effector glycosyltransferase was expanded in Chapter 3 to identify a novel target - the two-component response regulator OmpR. We show that the Salmonella T3SS effector glycosyltransferase SseK1 glycosylates the bacterial two-component response regulator OmpR on R15 and R122 arginine residues. OmpR Arg-glycosylation reduces the expression of ompF, a major outer membrane porin gene. Glycosylated OmpR has a lower affinity for the ompF promoter region than unglycosylated OmpR. Furthermore, the Salmonella [delta]sseK1 mutant strain had higher bile salt resistance and biofilm formation capacity than WT Salmonella, linking OmpR glycosylation to several important aspects of bacterial physiology. Our healthcare system faces a significant challenge from enteric gram-negative pathogens. Given the recent emergence of several multidrug-resistant enteric gram-negative strains, as well as other unique disease conditions where antibiotic administration is not feasible, novel alternatives to traditional antimicrobials are desirable. T3SS effector intrabacterial activity provides us with a unique opportunity to develop antivirulence compounds that can target T3SS effectors and effectively reduce their capacity to sustain infection. We previously performed high throughput screening assays to identify novel small molecule inhibitors of the T3SS effector NleB and its orthologs. Even though many of the effectors demonstrated promising in vitro results, they had limitations that prevented them from being considered viable therapeutics. Several of the identified inhibitors, for example, were poorly soluble, expensive to bulk synthesize, or lacked any prior safety and efficacy data. In Chapter 4, we discovered a potential activity for avasimibe, a previously identified acyl-coenzyme A:cholesterol acyltransferase inhibitor, in inhibiting the NleB and SseK arginine glycosyltransferases from Escherichia coli and Salmonella enterica, respectively, using high-throughput screening assays. Avasimibe inhibited the activity of the Citrobacter rodentium NleB, E. coli NleB1, and Salmonella enterica SseK1 enzymes without affecting the activity of the human serine/threonine N-acetylglucosamine (O-GlcNAc) transferase. At reasonably high dose, avasimibe was neither toxic to mammalian cells nor was it bactericidal. A dose of 10 µM avasimibe was sufficient to reduce S. enterica abundance in RAW264.7 macrophage-like cells. We conducted in vivo efficacy experiments using a mouse model in this study. Avasimibe intraperitoneal injection significantly reduced C. rodentium survival in mice, whether administered pre- or post-infection. We propose that avasimibe or related synthetic derivates may be useful in preventing or treating bacterial infections by inhibiting T3SS effector arginine glycosyltransferases, which are essential for virulence.
Keywords: T3SS; Salmonella; Citrobacter; Intrabacterial; NleC; Avasimibe